Pelaksanaan Pengadaan Tanah Bagi Pembangunan Jalan Tol Batang – Semarang Seksi II di Kelurahan Wonosari Kecamatan Ngaliyan Kota Semarang - gatot supriyanto .; Kushandajani . .; achmad taufiq . (Journal of Politic and Government Studies, 2017)
ABSTRACT Land Acquisition in the construction process for the public will be fraught with problems or conflictual. Basically, it because the public interest always sacrifice personal interests, with limited land availability. However, the process of the development of the Land Acquisition Toll Batang - Semarang Section II in Wonosari, there are some problems but can be addressed properly by the Land Procurement Team. This is a factor of researchers interested in researching the land acquisition process for the construction of Toll Batang - Semarang. This study used a qualitative approach with descriptive type.This research is compiled to reconstruct or redraw the land acquisition process for the construction of Toll Batang - Semarang Section II in Wonosari. The land acquisition was done in an effort to overcome bottlenecks and improve the economy. Research shows the procedure of land acquisition, land acquisition negotiations, resources, constraints, solutions, and the factors that support the achievement of the negotiations. It is concluded, based on the results of this study that the implementation of land acquisition negotiations in the construction of Toll Batang - Semarang Section II in Wonosari has been running smoothly. There are 244 plots of land belonging to residents were freed by the government.Recommendations given by the researchers, the government should be more active in the process or the approach of giving understanding to the community, and should be more transparent to citizens related to the price of Appraisal Team’s assessment about what the basis of the assessment team Appraisal. Research on the procurement of land in the development of Toll Batang - Semarang Section II in Wonosari can serve as an example of land acquisition activities. It can be managed as easily and reached an agreement between the Government and the citizens, i.e. particularly in addressing the development problems of the toll in other areas in Indonesia. Keyword : Land Acquisition, Public Interest, Negotiations.